Co-located perinatal psychiatry clinic: impact of adding a psychologist on clinical quality improvement metrics. (3rd April 2019) - Pawar, Deepa; Huang, Chiang-Ching; Wichman, Christina
Abstract: Purpose: To describe the impact of adding a psychologist (the intervention) to a co-located perinatal psychiatry clinic (PPC) in terms of effects on clinical quality improvement (QI) metrics. Methods: Six-month pre- and postintervention study design with measurement of QI metrics: number of unique patients treated; number of new and established visits; percent no-shows for new and established visits; and mean wait time to new visit. Results: Number of unique patients treated by the psychiatrist increased by 30%, from 90 preintervention to 118 postintervention ( p  = .06). Total number of visits completed by the psychiatrist increased by 20% from 174 preintervention to 208 postintervention. Mean wait time for new visits for a physician decreased from 20 days preintervention to 14 days postintervention, with a mean difference of 6.4 days ( p  = .0015). Percentage of no-shows for new visits increased slightly from 23% preintervention to 26% postintervention ( p  = .72). The percentage of no-shows for established visits decreased significantly from 22% preintervention to 10% postintervention ( p  < .005). Conclusions: By adding a psychologist to the co-located PPC, we improved quality of perinatal mental health care by improving efficiency, timeliness and patient-centered care. The psychiatrist saw a greater number of unique patients, decreased wait time to new visits and decreased no-show rates for established visits, likely by better matching patient needs with provider services. A psychologist could be a valuable addition to a PPC, given the shortage of psychiatrists in the United States.